Herpes Zoster with unusual clinical course. - Mazzotta, F.; Troccoli, T.; Garofalo, L.; Garofalo, L.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
A 18-year-old young man first presented erythematous and vesicular lesions with metameric distribution on the left deltoid region and upper limb. The lesions were associated with moderate pain of the scapular-humeral joint. These symptoms and signs led to diagnose herpes zoster and to prescribe Acyclovir per mouth. One month later, the patient came back reporting a flare up of the lesions seven days after their complete healing. On dermatological examination, only erythematous lesions were visible on the region that had been previously affected by herpes zoster. No diagnosis was made and the patient was invited to a further control. The latter was very useful fo the diagnosis, due to the occurrence of some psoriatic scales. A capillaroscopic study confirmed the diagnosis of eruptive zoster-like psoriasis suggesting a Koebner phenomenon induced by herpes zoster.